Two new species of Tanacetum (Anthemideae, Asteraceae) from western Iran - Rastegar, Azad; Maroofi, Hosein; Tabad, Mohammad Aref (Phytotaxa, 2022)
Tanacetum kurdistanicum and T. urmiense (Anthemideae, Asteraceae), from Abidar Mountain, and Dalanpar Mountain, respectively, are hereby described as new to science and illustrated. Their morphology and ecology are discussed in detail and a distribution map is provided.